MHealth interventions targeting movement behaviors in Asia: A scoping review. (19th December 2021) - Edney, Sarah; Chua, Xin Hui; Müller, Andre Matthias; Kui, Kiran Yan; Müller‐Riemenschneider, Falk
Summary: mHealth interventions can promote healthy movement behaviors (physical activity, sedentary behavior, and sleep). However, recent reviews include few studies from Asia, despite it being home to over 60% of the world population. The aim is to map the current evidence for mHealth interventions targeting movement behaviors in Asia. Six databases were searched up until August 2021. Included studies described an mHealth intervention targeting one or more movement behaviors, delivered in a country/territory in Asia, to a general population. A total of 3986 unique records were screened for eligibility in duplicate. Eighty studies with 1, 413, 652 participants were included. Most were randomized (38.8%) or quasi‐experimental (27.5%) trials. Studies were from 17 countries/territories (out of 55); majority were high‐ (65.0%) or upper middle‐income (28.7%). Physical activity was targeted most often (93.8%), few targeted sedentary behavior (7.5%), or sleep (8.8%). Most targeted one movement behavior (90.0%), and none targeted all three together. Interventions typically incorporated a single mHealth component (70.0%; app, pedometer, text messages, wearable) and were delivered remotely (66.3%). The average intervention length was 121.8 (SD 127.6) days. mHealth interventions in Asia have primarily targeted physical activity in high‐ and upper middle‐income countries. There are few interventions targeting sedentary behavior or sleep, and no interventions in low‐income countries.